The effect of smart TV-based mind mapping method on the critical reasoning dimension of children aged 5–6 years - Supiana; Nur Alim Amri; Musfira; Intisari (Universitas Islam Negeri Raden Intan Lampung, 2026)
Background: This study is motivated by the still low critical reasoning abilities of children in the learning process so that interesting and interactive learning methods and media are needed. Objective: This study aims to determine the effect of implementing the Smart TV-based mind mapping method on children's critical reasoning abilities. Methods: The research sample consisted of 15 children. Data collection techniques were carried out through pretest and posttest activities to measure children's critical reasoning abilities before and after the implementation of the learning method. The data obtained were analyzed using the Wilcoxon Signed Rank Test. This study contributes by integrating digital Smart TV media with traditional mind mapping to enhance cognitive engagement. Result: The results of the study showed that there was a significant increase in children's critical reasoning abilities, as indicated by the classroom's average score which rose from 26.47 (±12.81) in the pretest to 39.60 (±8.68) in the posttest. Furthermore, the Wilcoxon Signed Rank Test confirmed this positive shift with a calculated Z-value of -3.189 and a significance value of 0.001 (p < 0.05). Conclusion: Based on these statistical outcomes, it can be concluded that the implementation of the Smart TV-based mind mapping method exerts a significant effect on enhancing the critical reasoning abilities of young children.